Evaluation of Performance Parameters and Pollution Levels of Insulated Diesel Engine with Plastic Oil - Mohammad Attalique Rabbani, M.V.S Murali Krishna, P. Usha Sree (Mathematical Statistician and Engineering Applications, 2023)
The exhaust emissions from diesel engine cause health hazards, once they are inhaled in. They also cause environmental degradation. This paper aims at alternative fuel technology for diesel engine and environmental protection. Waste plastics are not biodegradable. They cause environmental disasters. Millions of cattle die every year after consuming these plastics. They produce toxic fumes, when they are burnt. However, when these plastics are converted into plastic oil by the process of pyrolysis, plastic oil can be used in diesel engines, as the properties of plastic oil are comparable with diesel fuel. In the context of fast depletion of fossil fuels, increase of economic burden on developing countries due to increase of cost of import of crude petroleum and increase of pollution levels with fossil fuels, the search for alternative fuels has become pertinent. Vegetable oils and alcohols are important substitutes for diesel fuel, as they are renewable in nature. Though vegetable oils have comparable properties with diesel fuel, however, they have high viscosity and low volatility causing combustion problems in diesel engines. Alcohols have high volatility but low Cetane number (a measure of combustion quality in diesel engine). Plastic oil derived from waste plastic collected from debris by the process of pyrolysis has equitant calorific value with diesel fuel. However, its viscosity is higher than diesel fuel calls for low heat rejection (LHR) diesel engine. The concept of LHR diesel engine is to minimize the heat flow to the coolant there by increase of thermal efficiency. This LHR engine is useful for burning high viscous & low calorific value fuels. LHR engine consisted of ceramic coated cylinder head engine. Theperformance parameters of brake thermal efficiency (BTE), exhaust gas temperature (EGT), volumetric efficiency and coolant load were evaluated at various values of brake mean effective pressure (BMEP) of the engine. Brake specific energy consumption (BSEC) was determined at full load operation of the engine with varied injection timing. The exhaust emissions of particulate matter, (PM), nitrogen oxide (NOx) levels, carbon monoxide (CO) levels and un-burnt hydro carbons (UBHC) levels were determined by sophisticated analyzers at different values of BMEP of the engine. Since, LHR engine gives higher NOx levels, selective catalytic reduction technique (SCRT) was applied to reduce nitrogen oxide levels. Data was compared with neat diesel operation on conventional engine (CE). Injection timing was varied with an electronic sensor. The performance of the both versions of the engine improved with supercharging of the engine.